Preparation method of composite copper foil for circuit

By forming a composite structure of the polydopamine-pyrrole organic layer and the nano-nickel metal layer on the surface of the copper foil, the conductive, easy and environmental protection problems of the composite copper foil separation layer in the prior art are solved, and efficient copper foil is achieved Disengagement and performance improvement.

CN119121342APending Publication Date: 2024-12-13GUANGDONG YINGHUA ELECTRONIC TECH CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411263317.4
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-09-10
Publication Date
2024-12-13

AI Technical Summary

Technical Problem

The existing composite copper foil's release layer is difficult to meet the requirements of excellent conductivity, easy disengagement, simple operation and environmental protection at the same time, and the release layer material is insufficient, which affects the performance of lithium-ion batteries.

Method used

Polydopamine and pyrrole are used to form an organic layer, and a nano-nickel metal layer is deposited on the surface of the copper foil. A new composite separation layer is formed through electrochemical means to enhance conductivity and adsorption capacity. The use of pollution-free nickel divalent sulfate as the electroplating solution. Ensure safety.

Benefits of technology

The bonding and disengagement performance between copper foil and ultra-thin copper foil is significantly improved, the conductivity and simplicity of operation are improved, and environmental protection and the stability of the disengagement layer are ensured.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119121342A_ABST
    Figure CN119121342A_ABST
Patent Text Reader

Abstract

The invention provides a preparation method of a composite copper foil for a circuit, and belongs to the technical field of preparation of composite copper foils. According to the invention, amino groups in polydopamine are chelated with metal nickel ions to form a compact nickel coating, so that the binding force and the separation performance of the carrier and the ultrathin copper foil are remarkably improved. The in-situ polymerization method is used for generating the polypyrrole layer on the surface of the carrier copper foil, and the operation is simple; by grafting polypyrrole with polydopamine, the adsorption capacity and conductivity of an organic layer to nickel ions are enhanced, the conductivity of the organic separation layer is quickly and efficiently improved by an electrochemical film forming method, and subsequent copper foil electroplating is facilitated. Pollution-free divalent nickel sulfate is used as a main component of the electroplating solution, so that the safety is ensured.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of composite copper foil preparation, and in particular relates to a method for preparing composite copper foil for circuits. Background Art

[0002] Electrolytic copper foil, as the negative electrode current collector, is a key raw material for preparing lithium-ion batteries. In recent years, with the rapid development of the new energy vehicle industry, lithium-ion batteries, as the power source of automobiles, have developed in the direction of smaller size and larger capacity, and higher requirements have been placed on the performance and thickness of copper foil. As the required thickness of copper foil decreases, the tensile strength also decreases, which can easily lead to copper foil breakage and affect performance. Carbon nanotubes play an important role in the field of composite materials due to their excellent electrical, thermal, and mechanical properties, and have become a hot topic of research at home and abroad.

[0003] However, the existing ultra-thin composite copper foil is often prepared by the method of attaching a carrier, usually using a thicker electrolytic copper foil as a carrier, and then forming a release layer on the carrier, and then depositing the ultra-thin copper foil. When in use, the ultra-thin copper foil needs to be pressed with the resin, and then the carrier copper foil layer is peeled off. The preparation of the release layer is the key to the production of ultra-thin copper foil, which is mainly divided into inorganic release layer, organic release layer and composite release layer. The inorganic release layer has good conductivity, but it is difficult to release; the organic release layer mostly uses nitrogen-containing, sulfur-containing compounds and carboxylic acids, but has poor conductivity and uneven adsorption; the composite release layer combines the organic layer and the inorganic layer, and has their own advantages, but there is a problem of uneven release.

[0004] In order to improve the performance of the release layer, some patented technologies in recent years have proposed new methods. For example, a composite release layer of crystalline nickel and amorphous nickel plating is used. The van der Waals force between the amorphous nickel plating and the copper foil is weak, easy to detach and the interface is pure; another method is to achieve self-detachment of the copper foil by electro-depositing discrete Cr crystal nuclei. The use of trivalent chromium is more environmentally friendly, but the stability of its solution is poor. These methods have improved the performance and environmental friendliness of the release layer to varying degrees, but each has its own limitations.

[0005] Patent CN108330517A discloses a plating solution and preparation method for a carrier copper foil release layer, which uses potassium hydrogen tartrate, zinc sulfate and other additives to prepare the plating solution, and immerses the carrier copper in the solution, so as to electroplate a nano-composite zinc-plated release layer on the carrier copper foil, and the release layer is extremely thin and evenly distributed. However, the adhesion between the release layer and the copper foil is too strong, and the release effect after hot pressing is not ideal, and the zinc-plated layer may damage the ultra-thin copper foil.

[0006] The main challenge of the current research on composite release layers is to simultaneously meet the four requirements of excellent conductivity, easy release, simple operation and environmental protection. These four requirements often conflict with each other, so it is necessary to develop a composite copper foil and its preparation method that has excellent conductivity, easy release, simple operation and environmental protection, and good stability of the release layer material. Summary of the invention

[0007] Based on the deficiencies in the prior art, the present invention aims to provide a composite copper foil and a preparation method thereof which has excellent conductivity, is easy to detach, is simple to operate and is environmentally friendly, and has good stability of the detachment layer material. In the implementation process of the present invention, the adsorption capacity of metal ions is significantly improved by grafting polypyrrole, and polypyrrole has excellent conductive properties and can enhance the conductive properties of the organic layer. In addition, polydopamine and pyrrole are combined on the surface of the copper foil by electrochemical means, and then a nano-nickel metal layer is deposited on the surface of the composite film to form a new composite detachment layer.

[0008] In order to achieve the above object, the present invention adopts the following technical solution:

[0009] A method for preparing a composite copper foil for circuits comprises the following steps:

[0010] (1) Pretreatment of carrier copper foil;

[0011] (2) Preparation of copper foil containing organic layer carrier:

[0012] (2.1) Dissolve polydopamine in an organic acid solution, add ethanol, and heat and stir until completely dissolved to obtain solution 1;

[0013] (2.2) adding a crosslinking agent to solution 1 and continuing stirring to form a polydopamine pretreatment solution;

[0014] (2.3) dissolving pyrrole in a phosphoric acid solution to form a pyrrole solution;

[0015] (2.4) adding the polydopamine pretreatment solution to the pyrrole solution to form an electrodeposition solution;

[0016] (2.5) The pretreated carrier copper foil is immersed in an electroplating solution to perform an electroplating treatment, thereby obtaining a carrier copper foil containing an organic layer.

[0017] (3) Preparation of copper foil containing metal-plated carrier:

[0018] (3.1) Add nickel sulfate, boric acid, ammonium acetate and sodium dodecyl sulfate into water and stir to dissolve to form a metal plating solution;

[0019] (3.2) immersing the carrier copper foil of the electrodeposited organic layer into a metal electroplating solution for electroplating to obtain a carrier copper foil containing a metal-plated layer;

[0020] (4) Preparation of carrier copper foil containing ultra-thin copper foil layer

[0021] (4.1) adding copper sulfate pentahydrate, collagen, hydroxyethyl cellulose and sodium chloride into water to obtain a copper plating solution;

[0022] (4.2) The metal-plated carrier copper foil is immersed in a copper plating solution and electroplated to obtain a carrier copper foil containing an ultra-thin copper foil layer.

[0023] in,

[0024] The carrier copper foil pretreatment described in step (1) above comprises the following specific steps:

[0025] (1.1) preparing an alkaline treatment solution;

[0026] (1.2) Soaking the carrier copper foil in an alkaline treatment solution;

[0027] (1.3) Use ethanol and water to wash in sequence to obtain a pretreated carrier copper foil.

[0028] The alkaline treatment solution described in step (1.1) is an ethanol aqueous solution of NaOH and Na2CO3, or an ethanol aqueous solution of Ba(OH)2 and NaHCO3, or an ethanol aqueous solution of KOH and Na2CO3.

[0029] The concentration of NaOH, Ba(OH)2 or KOH in the alkaline treatment solution is 1-3M, preferably 2M;

[0030] The concentration of Na2CO3 or NaHCO3 in the alkaline treatment solution is 0.25-0.75M, preferably 0.5M;

[0031] The volume ratio of ethanol to water is 2-4:1, preferably 3:1.

[0032] The soaking time in step (1.2) is 8-15 minutes, preferably 10 minutes.

[0033] In the present invention, the use of alkaline solution to pretreat the carrier copper foil can effectively remove surface grease and impurities, and can also break the ester bonds of the grease to form functional groups such as carboxyl and hydroxyl groups to improve the adhesion of the base film.

[0034] The organic acid in the above step (2.1) is acetic acid; the concentration of the acetic acid is 1-5wt%.

[0035] The mass volume ratio of the polydopamine, acetic acid solution and anhydrous ethanol described in the above step (2.1) is 25-40g:80-90ml:10-20ml; preferably 30g:85ml:15ml.

[0036] The heating temperature in the above step (2.1) is 50-80°C, preferably 60°C.

[0037] The cross-linking agent is selected from any one of glutaraldehyde and dopamine, and its concentration is 4-8wt%.

[0038] The mass ratio of polydopamine to cross-linking agent in the polydopamine pretreatment solution is 50-80:1, preferably 75:1.

[0039] The concentration of pyrrole in the above step (2.3) is 0.1-0.5M; the concentration of phosphoric acid is 0.1-0.5M.

[0040] The concentration of polydopamine in the electrodeposition solution in step (2.4) is 10-20% (w / v); preferably 15%

[0041] The molar ratio of pyrrole to phosphoric acid in the above step (2.3) is 1:1.4-2.

[0042] The electrodeposition described in the above step (2.5) was carried out by constant current method with a current density of 0.03-0.09 mA / cm 2 , the electrodeposition time is 6min-3h.

[0043] The mass ratio of nickel sulfate, boric acid, ammonium acetate and sodium dodecyl sulfate described in the above step (3.1) is 20-100:80:36:0.05; preferably 60:80:36:0.05.

[0044] The electroplating temperature in the above step (3.2) is 10-60°C; the current density is 0.4-1.2 mA / cm 2 , the plating time is 4-35s.

[0045] The mass ratio of copper sulfate pentahydrate, collagen, hydroxyethyl cellulose and sodium chloride in the above step (4.1) is 1.566×10 4 :0.5-1.5:0.5-1.5:1.5-4.5; preferably 1.566×10 4 :1:1:3.

[0046] The electroplating temperature in the above step (4.2) is 10-60°C; the current density is 360-440 mA / cm 2 , the plating time is 10-30s.

[0047] The method for preparing the composite copper foil further comprises (5) anti-oxidation treatment;

[0048] The anti-oxidation treatment comprises the following specific steps:

[0049] (5.1) immersing the carrier copper foil containing the ultra-thin copper foil layer obtained in step (4) into an anti-oxidation solution for 10 seconds;

[0050] (5.2) The soaked composite copper foil is squeezed out of the liquid by a water-collecting roller and blown dry under 80°C hot air to complete the anti-oxidation treatment.

[0051] The anti-oxidation liquid described in step (5.1) is a mixture of benzotriazole and benzoic acid, and the concentration ratio of the two is 1:1.

[0052] The composite copper foil prepared by the above method comprises, from top to bottom, a carrier copper foil layer 1, an organic layer 2, a metal plating layer 3 and an ultra-thin copper foil layer 4.

[0053] Compared with the prior art, the present invention has the following beneficial effects:

[0054] The present invention utilizes amino groups in polydopamine to chelate with metal nickel ions to form a dense nickel plating layer, which significantly improves the bonding strength and detachment performance of the carrier copper foil and the ultra-thin copper foil. The in-situ polymerization method is used to generate a polypyrrole layer on the surface of the carrier copper foil, which is simple to operate; by grafting polypyrrole with polydopamine, the adsorption capacity and conductivity of the organic layer to nickel ions are enhanced, and the electrochemical film forming method quickly and efficiently improves the conductivity of the organic layer, which is convenient for subsequent electroplating of copper foil. Non-polluting divalent nickel sulfate is used as the main component of the electroplating solution to ensure safety. BRIEF DESCRIPTION OF THE DRAWINGS

[0055] Figure 1 Schematic diagram of the structure of the carrier ultra-thin copper foil of the present invention

[0056] Figure numerals: 1 - carrier copper foil layer; 2 - organic layer; 3 - metal plating layer; 4 - ultra-thin copper foil layer. DETAILED DESCRIPTION

[0057] The following non-limiting examples are intended to help relevant technicians fully understand the present invention, but do not constitute a limitation thereto. The following content is only an example of the scope of protection of the present invention, and professionals can make various modifications based on the disclosed information, and these modifications should be considered within the scope of protection of the present invention.

[0058] Example 1 A method for preparing a composite copper foil for circuits

[0059] The steps include:

[0060] (1) Carrier copper foil pretreatment:

[0061] (1.1) preparing an alkaline treatment solution: preparing an ethanol aqueous solution of NaOH and Na2CO3, wherein the concentration of NaOH is 2 M, the concentration of Na2CO3 is 0.5 M, and the volume ratio of ethanol to water is 3:1;

[0062] (1.2) Soak the carrier copper foil in an alkaline treatment solution for 10 minutes;

[0063] (1.3) Take out the carrier copper foil, and wash it with ethanol and water in sequence to obtain a pretreated carrier copper foil.

[0064] (2) Preparation of copper foil containing organic layer carrier:

[0065] 30 g of polydopamine was dissolved in 85 mL of 2.5 wt% acetic acid solution, 15 mL of anhydrous ethanol was added, and the mixture was heated and stirred at 65° C. for 1 h to completely decompose the polydopamine by acid to obtain solution 1;

[0066] (2.2) adding 5 g of 8% glutaraldehyde (the mass ratio of polydopamine to glutaraldehyde is 75:1) to solution 1, and continuing stirring for 2 h to obtain a polydopamine pretreatment solution, wherein the polydopamine concentration is 10% (w / v);

[0067] (2.3) Mix 20 mL of pyrrole (concentration 0.4 M) and 80 mL of phosphoric acid (concentration 0.2 M) to obtain a pyrrole solution;

[0068] (2.4) adding the polydopamine pretreatment solution of step (2.2) to the pyrrole solution of step (2.3) to obtain an electrodeposition solution (the concentration of polydopamine is 15% (w / v);

[0069] (2.5) Using constant current deposition method, the current density is 0.04mA / cm 2 , the electrodeposition time is 40 min, and a carrier copper foil carrying an organic layer is obtained;

[0070] (2.6) washing the copper foil containing the organic layer carrier with anhydrous ethanol and deionized water respectively, and drying at 90° C.;

[0071] (3) Preparation of copper foil containing metal-plated carrier:

[0072] (3.1) Add 6.0 g of nickel sulfate, 8.0 g of boric acid, 3.6 g of ammonium acetate and 0.005 g of sodium dodecyl sulfate to 100 mL of water, stir and dissolve to obtain a metal plating solution;

[0073] (3.2) The copper foil of the electrodeposited organic layer was immersed in a metal electroplating solution for electroplating. The electroplating temperature was 50°C and the current density was 0.5 mA / cm 2, the electroplating time is 30s, and the copper foil containing the metal-plated carrier is obtained;

[0074] (4) Preparation of carrier copper foil containing ultra-thin copper foil layer

[0075] (4.1) Add 7.83 g of copper sulfate pentahydrate, 0.0005 g of collagen, 0.0005 g of hydroxyethyl cellulose, and 0.0015 g of sodium chloride to 100 mL of water to obtain a copper plating solution;

[0076] (4.2) The metal-plated copper foil is immersed in a copper plating solution for electroplating at a temperature of 50°C and a current density of 400 mA / cm 2 , the electroplating time is 20s, and the carrier copper foil containing the ultra-thin copper foil layer is obtained;

[0077] (5) Antioxidant treatment:

[0078] (5.1) Immerse the carrier copper foil containing the ultra-thin copper foil layer in an anti-oxidation solution (a mixture of 1 g / L benzotriazole and 1 g / L benzoic acid) for 10 seconds;

[0079] (5.2) Squeeze out the liquid through a water-collecting roller and blow dry under hot air at 80°C to complete the anti-oxidation treatment;

[0080] The composite copper foil after anti-oxidation treatment was pressed onto the PCB board at 200°C for 1.5 hours. After curing, the carrier copper foil was mechanically separated and removed to obtain an ultra-thin copper foil.

[0081] Example 2 A method for preparing a composite copper foil for circuits

[0082] The composite copper foil comprises, from top to bottom, a carrier copper foil layer 1, an organic layer 2, a metal plating layer 3 and an ultra-thin copper foil layer 4.

[0083] The preparation method of the composite copper foil comprises the following steps:

[0084] (1) Carrier copper foil pretreatment:

[0085] (1.1) preparing an alkaline treatment solution: preparing an ethanol aqueous solution of Ba(OH)2 and NaHCO3, wherein the concentration of Ba(OH)2 is 1 M, the concentration of NaHCO3 is 0.25 M, and the volume ratio of ethanol to water is 2:1;

[0086] (1.2) Soak the carrier copper foil in an alkaline treatment solution for 15 minutes;

[0087] (1.3) Take out the carrier copper foil, and wash it with ethanol and water in sequence to obtain a pretreated carrier copper foil.

[0088] (2) Preparation of copper foil containing organic layer carrier:

[0089] (2.1) Dissolve 25 g of polydopamine in 80 mL of 5 wt% acetic acid solution, add 20 mL of anhydrous ethanol, heat and stir at 60° C. for 1 h until the polydopamine is completely acid-decomposed to obtain solution 1;

[0090] (2.2) adding 10 g of 5% glutaraldehyde (the mass ratio of polydopamine to glutaraldehyde is 50:1) to solution 1, and continuing stirring for 2 h to obtain a polydopamine pretreatment solution;

[0091] (2.3) Mix 40 mL of pyrrole (concentration 0.3 M) and 60 mL of phosphoric acid (concentration 0.3 M) to obtain a pyrrole solution;

[0092] (2.4) adding the polydopamine pretreatment solution of step (2.2) to the pyrrole solution of step (2.3) to obtain an electrodeposition solution (the concentration of polydopamine is 12.5% ​​(w / v);

[0093] (2.5) Using constant current deposition method, the current density is 0.03mA / cm 2 , the electrodeposition time is 2h, and a carrier copper foil carrying an organic layer is obtained;

[0094] (2.6) washing the copper foil containing the organic layer carrier with anhydrous ethanol and deionized water respectively, and drying at 90° C.;

[0095] (3) Preparation of copper foil containing metal-plated carrier:

[0096] (3.1) Add 2.0 g of nickel sulfate, 8.0 g of boric acid, 3.6 g of ammonium acetate and 0.005 g of sodium dodecyl sulfate to 100 mL of water and stir to dissolve to obtain a metal plating solution;

[0097] (3.2) The copper foil of the electrodeposited organic layer was immersed in a metal electroplating solution for electroplating. The electroplating temperature was 10°C and the current density was 1.2 mA / cm 2 , the electroplating time is 35s, and the copper foil containing the metal-plated carrier is obtained;

[0098] (4) Preparation of carrier copper foil containing ultra-thin copper foil layer

[0099] (4.1) Add 7.83 g of copper sulfate pentahydrate, 0.00025 mg of collagen, 0.00025 mg of hydroxyethyl cellulose, and 0.0075 mg of sodium chloride to 100 mL of water to obtain a copper plating solution;

[0100] (4.2) The metal-plated copper foil is immersed in a copper plating solution for electroplating. The electroplating temperature is 10°C and the current density is 360 mA / cm 2, the electroplating time is 10s, and the carrier copper foil containing the ultra-thin copper foil layer is obtained;

[0101] (5) Antioxidant treatment:

[0102] (5.1) Immerse the carrier copper foil containing the ultra-thin copper foil layer in an anti-oxidation solution (a mixture of 1 g / L benzotriazole and 1 g / L benzoic acid) for 10 seconds;

[0103] (5.2) Squeeze out the liquid through a water-collecting roller and blow dry under hot air at 80°C to complete the anti-oxidation treatment;

[0104] The composite copper foil after anti-oxidation treatment was pressed onto the PCB board at 200°C for 1.5 hours. After curing, the carrier copper foil was mechanically separated and removed to obtain an ultra-thin copper foil.

[0105] Example 3 A method for preparing a composite copper foil for circuits

[0106] The composite copper foil comprises, from top to bottom, a carrier copper foil layer 1, an organic layer 2, a metal plating layer 3 and an ultra-thin copper foil layer 4.

[0107] The preparation method of the composite copper foil comprises the following steps:

[0108] (1) Carrier copper foil pretreatment:

[0109] (1.1) preparing alkaline treatment solution: preparing ethanol aqueous solution of KOH and Na2CO3, the concentration of KOH is 2M, the concentration of Na2CO3 is 0.5M, and the volume ratio of ethanol to water is 3:1;

[0110] (1.2) Soak the carrier copper foil in an alkaline treatment solution for 10 minutes;

[0111] (1.3) Take out the carrier copper foil, and wash it with ethanol and water in sequence to obtain a pretreated carrier copper foil.

[0112] (2) Preparation of copper foil containing organic layer carrier:

[0113] (2.1) Dissolve 40 g of polydopamine in 90 mL of 1 wt% acetic acid solution, add 10 mL of anhydrous ethanol, and heat and stir at 80° C. for 1 h to completely decompose the polydopamine to obtain solution 1;

[0114] (2.2) adding 6.25 g of dopamine with a concentration of 8% (the mass ratio of polydopamine to dopamine is 80:1) to solution 1, and continuing stirring for 2 h to obtain a polydopamine pretreatment solution;

[0115] (2.3) Mix 35 mL of pyrrole (concentration 0.5 M) and 65 mL of phosphoric acid (concentration 0.5 M) to obtain a pyrrole solution;

[0116] (2.4) adding the polydopamine pretreatment solution of step (2.2) to the pyrrole solution of step (2.3) to obtain an electrodeposition solution (the concentration of polydopamine is 20% (w / v);

[0117] (2.5) Using constant current deposition method, the current density is 0.06mA / cm 2 , the electrodeposition time is 60 min, and a carrier copper foil carrying an organic layer is obtained;

[0118] (2.6) washing the copper foil containing the organic layer carrier with anhydrous ethanol and deionized water respectively, and drying at 90° C.;

[0119] (3) Preparation of copper foil containing metal-plated carrier:

[0120] (3.1) Add 8.0 g of nickel sulfate, 8.0 g of boric acid, 3.6 g of ammonium acetate and 0.005 g of sodium dodecyl sulfate to 100 mL of water and stir to dissolve to obtain a metal plating solution;

[0121] (3.2) The copper foil of the electrodeposited organic layer was immersed in a metal electroplating solution for electroplating. The electroplating temperature was 30°C and the current density was 1.0 mA / cm 2 , the electroplating time is 25s, and the copper foil containing the metal-plated carrier is obtained;

[0122] (4) Preparation of carrier copper foil containing ultra-thin copper foil layer

[0123] (4.1) Add 7.83 g of copper sulfate pentahydrate, 0.0010 mg of collagen, 0.0010 mg of hydroxyethyl cellulose, and 0.0030 mg of sodium chloride to 100 mL of water to obtain a copper plating solution;

[0124] (4.2) The metal-plated carrier copper foil is immersed in a copper plating solution for electroplating at a temperature of 30°C and a current density of 420 mA / cm 2 , the electroplating time is 25s, and the carrier copper foil containing the ultra-thin copper foil layer is obtained;

[0125] (5) Antioxidant treatment:

[0126] (5.1) Immerse the carrier copper foil containing the ultra-thin copper foil layer in an anti-oxidation solution (a mixture of 1 g / L benzotriazole and 1 g / L benzoic acid) for 10 seconds;

[0127] (5.2) Squeeze out the liquid through a water-collecting roller and blow dry under hot air at 80°C to complete the anti-oxidation treatment;

[0128] The composite copper foil after anti-oxidation treatment was pressed onto the PCB board at 200°C for 1.5 hours. After curing, the carrier copper foil was mechanically separated and removed to obtain an ultra-thin copper foil.

[0129] Example 4: A method for preparing a composite copper foil for circuits

[0130] The composite copper foil comprises, from top to bottom, a carrier copper foil layer 1, an organic layer 2, a metal plating layer 3 and an ultra-thin copper foil layer 4.

[0131] The preparation method of the composite copper foil comprises the following steps:

[0132] (1) Carrier copper foil pretreatment:

[0133] (1.1) preparing an alkaline treatment solution: preparing an ethanol aqueous solution of KOH and NaHCO3, wherein the concentration of KOH is 2.5 M, the concentration of NaHCO3 is 0.35 M, and the volume ratio of ethanol to water is 3.5:1;

[0134] (1.2) Soak the carrier copper foil in an alkaline treatment solution for 10 minutes;

[0135] (1.3) Take out the carrier copper foil, and wash it with ethanol and water in sequence to obtain a pretreated carrier copper foil.

[0136] (2) Preparation of copper foil containing organic layer carrier:

[0137] (2.1) Dissolve 36 g of polydopamine in 80 mL of 3 wt% acetic acid solution, add 20 mL of anhydrous ethanol, heat and stir at 70°C for 1 h to completely decompose the polydopamine, and obtain solution 1;

[0138] (2.2) adding 15 g of 4% glutaraldehyde (the mass ratio of polydopamine to glutaraldehyde is 60:1) to solution 1, and continuing stirring for 2 h to obtain a polydopamine pretreatment solution, wherein the polydopamine concentration is 10% (w / v);

[0139] (2.3) Mix 30 mL of pyrrole (concentration 0.5 M) and 70 mL of phosphoric acid (concentration 0.3 M) to obtain a pyrrole solution;

[0140] (2.4) adding the polydopamine pretreatment solution of step (2.2) to the pyrrole solution of step (2.3) to obtain an electrodeposition solution (the concentration of polydopamine is 18% (w / v);

[0141] (2.5) Constant current deposition method was used with a current density of 0.08 mA / cm 2 , the electrodeposition time is 90 min, and a carrier copper foil carrying an organic layer is obtained;

[0142] (2.6) washing the copper foil containing the organic layer carrier with anhydrous ethanol and deionized water respectively, and drying at 90° C.;

[0143] (3) Preparation of copper foil containing metal-plated carrier:

[0144] (3.1) Add 10.0 g of nickel sulfate, 8.0 g of boric acid, 3.6 g of ammonium acetate and 0.005 g of sodium dodecyl sulfate to 100 mL of water, stir and dissolve to obtain a metal plating solution;

[0145] (3.2) The copper foil of the electrodeposited organic layer was immersed in a metal plating solution for electroplating. The electroplating temperature was 45°C and the current density was 0.8 mA / cm 2 , the electroplating time is 25s, and the copper foil containing the metal-plated carrier is obtained;

[0146] (4) Preparation of carrier copper foil containing ultra-thin copper foil layer

[0147] (4.1) Add 7.83 g of copper sulfate pentahydrate, 0.0005 mg of collagen, 0.0005 mg of hydroxyethyl cellulose, and 0.0015 mg of sodium chloride to 100 mL of water to obtain a copper plating solution;

[0148] (4.2) The metal-plated copper foil is immersed in a copper plating solution for electroplating at a temperature of 30°C and a current density of 440 mA / cm 2 , the electroplating time is 18s, and the carrier copper foil containing the ultra-thin copper foil layer is obtained;

[0149] (5) Antioxidant treatment:

[0150] (5.1) Immerse the carrier copper foil containing the ultra-thin copper foil layer in an anti-oxidation solution (a mixture of 1 g / L benzotriazole and 1 g / L benzoic acid) for 10 seconds;

[0151] (5.2) Squeeze out the liquid through a water-collecting roller and blow dry under hot air at 80°C to complete the anti-oxidation treatment;

[0152] (6) Pressing:

[0153] The composite copper foil after anti-oxidation treatment was pressed onto the PCB board at 200°C for 1.5 hours. After curing, the carrier copper foil was mechanically separated and removed to obtain an ultra-thin copper foil.

[0154] Comparative Example 1

[0155] The only difference from Example 1 is that polydopamine is replaced by an equal amount of chitosan, and the rest is the same as Example 1.

[0156] Comparative Example 2

[0157] The only difference from Example 1 is that polydopamine is replaced by glucosamine, and the rest is the same as Example 1.

[0158] Comparative Example 3

[0159] The only difference from Example 1 is that the amount of polydopamine added in step (2.1) is 50 g, and the rest is the same as Example 1.

[0160] Comparative Example 4

[0161] The only difference from Example 1 is that the amount of polydopamine added in step (2.1) is 10 g, and the rest is the same as Example 1.

[0162] Comparative Example 5

[0163] The only difference from Example 1 is that no polydopamine is added to the organic layer, and only the pyrrole solution is electrodeposited to obtain the polypyrrole layer; specifically:

[0164] (2) Preparation of copper foil containing organic layer carrier:

[0165] (2.1) Mix 20 mL of pyrrole (concentration 0.4 M) and 80 mL of phosphoric acid (concentration 0.2 M) to obtain a pyrrole solution, which is the electrodeposition solution;

[0166] (2.2) Using constant current deposition method, the current density is 0.04mA / cm 2 , the electrodeposition time is 40 min, and a carrier copper foil carrying an organic layer is obtained;

[0167] (2.3) The copper foil containing the organic layer carrier is cleaned with anhydrous ethanol and deionized water respectively, and dried at 90°C.

[0168] Comparative Example 6

[0169] The only difference from Example 1 is that step (2) is not included, that is, the preparation of the organic layer carrier copper foil is not included, and the other steps are the same as Example 1.

[0170] Comparative Example 7

[0171] The only difference from Example 1 is that step (3) is not included, that is, the preparation of the metal-plated carrier copper foil is not included, and the other steps are the same as Example 1.

[0172] The relevant performance characterization results of the ultra-wave copper foil prepared in the comparative example of the embodiment of the present invention are shown in Table 1.

[0173] Table 1 Composite copper foil performance characterization results

[0174]

[0175] Comparative Example 1 can be seen from Example 1 that when chitosan is used, it is difficult to detach. This is because chitosan is a natural polymer with strong adhesion. After combining with the copper surface, a stable interface is formed, making it difficult to detach. In addition, during the preparation of the copper foil, chitosan may react with the copper surface by chemical crosslinking or physical crosslinking, further enhancing its binding force, making subsequent detachment more difficult.

[0176] Comparative Example 2 Compared with Example 1, an equal amount of glucosamine is used to replace polydopamine. Glucosamine may form a chelate with copper ions, and this binding mode is relatively stable and is difficult to be separated by simple cleaning or conventional chemical treatment. Glucosamine forms a chemical bond with the copper surface through its amino group, and this bonding strength is relatively large and is not easy to break. Its break-off strength also has a certain degree of decline, and the cost is relatively high, which is not suitable for industrial production.

[0177] In comparative examples 3, 4 and Example 1, it can be seen that the amount of polydopamine has a significant effect on the detachment performance of the ultra-thin copper foil. When the amount of polydopamine is too low, the generated organic layer is too thin, resulting in insufficient adsorption capacity for nickel. When the amount is too high, the generated organic layer is too thick, resulting in uneven copper plating, which is also not conducive to the detachment of the ultra-thin copper foil. In addition, the amount of polydopamine directly affects the concentration of polydopamine and thus has an adverse effect on the detachment of the carrier copper foil, which may be related to the solubility of polydopamine. Reduced solubility may lead to a decrease in film quality, thereby affecting the uniformity of subsequent copper plating, causing thinning of certain areas of the copper foil, and thus making the detachment process uneven.

[0178] Compared with Example 1, in Comparative Example 5, polydopamine was not used, and the adsorption capacity of polypyrrole in the organic layer to nickel was insufficient. The organic layer partially adhered to the copper layer, resulting in incomplete detachment, and detachment could not be performed.

[0179] Comparative Example 6 Compared with Example 1, the organic layer is generally used to improve the release performance and reduce the possibility of the copper foil adhering to other materials during the preparation process. The absence of the organic layer leads to a decrease in the release performance and increases the difficulty of operation during the preparation process.

[0180] The metal nickel plating layer generally helps to enhance the adhesion and stability between the layer and the copper foil.Comparative Example 7 Compared with Example 1, the lack of the metal nickel plating layer may lead to a weakened bonding force between the release layer and the copper foil, thereby possibly reducing the reliability and performance stability of the release layer.

[0181] Finally, it should be pointed out that the above content is only used to illustrate the technical solution of the present invention and does not limit the protection scope of the present invention. For ordinary technicians in this field, simple modifications or equivalent substitutions do not violate the essence and scope of the technical solution of the present invention.

Claims

1. A method for preparing a composite copper foil for circuits, characterized in that: The steps include: (1) Pretreatment of carrier copper foil; (2) Preparation of copper foil containing organic layer carrier: (2.1) Dissolve polydopamine in an organic acid solution, add ethanol, and heat and stir until completely dissolved to obtain solution 1; (2.2) adding a crosslinking agent to solution 1 and continuing stirring to form a polydopamine pretreatment solution; (2.3) dissolving pyrrole in a phosphoric acid solution to form a pyrrole solution; (2.4) adding the polydopamine pretreatment solution to the pyrrole solution to form an electrodeposition solution; (2.5) immersing the pretreated carrier copper foil in an electrodeposition solution to perform an electrodeposition treatment, thereby obtaining a carrier copper foil containing an organic layer; (3) Preparation of copper foil containing metal-plated carrier: (3.1) Add nickel sulfate, boric acid, ammonium acetate and sodium dodecyl sulfate into water and stir to dissolve to form a metal plating solution; (3.2) immersing the carrier copper foil of the electrodeposited organic layer into a metal electroplating solution for electroplating to obtain a carrier copper foil containing a metal-plated layer; (4) Preparation of carrier copper foil containing ultra-thin copper foil layer: (4.1) adding copper sulfate pentahydrate, collagen, hydroxyethyl cellulose and sodium chloride into water to obtain a copper plating solution; (4.2) The metal-plated carrier copper foil is immersed in a copper plating solution and electroplated to obtain a carrier copper foil containing an ultra-thin copper foil layer.

2. The preparation method according to claim 1, characterized in that: The mass volume ratio of the polydopamine, acetic acid solution and anhydrous ethanol described in step (2.1) is 25-40g:80-90ml:10-20ml.

3. The preparation method according to claim 2, characterized in that: The mass volume ratio of polydopamine, acetic acid solution and anhydrous ethanol described in step (2.1) is 30g:85ml:15ml.

4. The preparation method according to claim 1, characterized in that: The mass ratio of polydopamine to cross-linking agent in the polydopamine pretreatment solution described in step (2.2) is 50-80:

1.

5. The preparation method according to claim 4, characterized in that: The mass ratio of polydopamine to cross-linking agent in the polydopamine pretreatment solution described in step (2.2) is 75:

1.

6. The preparation method according to claim 1, characterized in that: The concentration of polydopamine in the electrodeposition solution described in step (2.4) is 10-20%, w / v.

7. The preparation method according to claim 1, characterized in that: The mass ratio of nickel sulfate, boric acid, ammonium acetate and sodium dodecyl sulfate described in step (3.1) is 20-100:80:36:0.

05.

8. The composite copper foil according to claim 1, characterized in that: The mass ratio of copper sulfate pentahydrate, collagen, hydroxyethyl cellulose and sodium chloride in step (4.1) is 1.566×10 4 :0.5-1.5:0.5-1.5:1.5-4.

5.

9. The preparation method according to claim 1, characterized in that: The method for preparing the composite copper foil further includes (5) anti-oxidation treatment.

10. A composite copper foil prepared by the preparation method according to any one of claims 1 to 9, characterized in that: The composite copper foil comprises, from top to bottom, a carrier copper foil layer 1, an organic layer 2, a metal plating layer 3 and an ultra-thin copper foil layer 4.